2012
DOI: 10.1590/s0100-83582012000400023
|View full text |Cite
|
Sign up to set email alerts
|

Mobilidade do ametryn em latossolos brasileiros

Abstract: RESUMO -O conhecimento dos fatores que influenciam a lixiviação dos herbicidas no solo possibilita o uso seguro do produto do ponto de vista ambiental, além de ser fundamental para que se façam recomendações tecnicamente corretas. Objetivou-se com este trabalho avaliar a lixiviação do ametryn em quatro solos brasileiros, com diferentes características físico-químicas, e comparar o método cromatográfico com o biológico em estudos de mobilidade desse herbicida. Os substratos avaliados foram: Latossolo Vermelho-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
(18 reference statements)
1
5
0
2
Order By: Relevance
“…In addition, bioassay proved to be more sensitive for the detection of CMZ in the soil columns, showing the presence of the herbicide in the 25-30 cm segment from unamended soil columns. The higher sensitivity of the greenhouse bioassay method compared to the chromatographic analysis was also observed by Silva et al 38 In the evaluation of ametryne leaching in Brazilian soils, the authors observed that the species Cucumis sativus was able to detect the herbicide in greater depths than chromatographic analysis, showing the feasibility of using bioassays to obtain complementary information of pesticide leaching.…”
Section: Bioavailability Assessment Of Cmz Along the Columnsupporting
confidence: 52%
“…In addition, bioassay proved to be more sensitive for the detection of CMZ in the soil columns, showing the presence of the herbicide in the 25-30 cm segment from unamended soil columns. The higher sensitivity of the greenhouse bioassay method compared to the chromatographic analysis was also observed by Silva et al 38 In the evaluation of ametryne leaching in Brazilian soils, the authors observed that the species Cucumis sativus was able to detect the herbicide in greater depths than chromatographic analysis, showing the feasibility of using bioassays to obtain complementary information of pesticide leaching.…”
Section: Bioavailability Assessment Of Cmz Along the Columnsupporting
confidence: 52%
“…The sensitivity of the biological method to detect the presence of sulfentrazone in the soil makes it a possible option to use in leaching tests of this product. The association between instrumental and biological methods has the advantage of reducing the cost of labor, as well as the number of chemical analyses (Silva et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…This technique is based on the use of plants that are sensitive to the tested herbicides, so that the presence of residues in the soil is evidenced by changes in physiological and morphological characteristics of the key-plant species. In the literature, several studies involving bioassays for determination of leaching of herbicides such as amethrin (Silva et al, 2012), sulfentrazone (Silva Junior et al, 2016), imazethapyr, imazapyque and imazapyr (Bundt et al 2014) have been reported. On the other hand, to test the efficiency of this method, it would be interesting to compare it with already consolidated methods such as HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…Nos trabalhos revisados foi verificado que intoxicação e massa seca de Research, Society and Development, v. 9, n. 9, e999998123, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.8123 parte aérea são as variáveis mais discriminadoras de resíduos de herbicidas (Tabela 1) (Freitas et al, 2014;Melo et al, 2010). Research, Society and Development, v. 9, n. 9, e999998123, 2020 (CC BY 4.0 ametryn Arenoso/Argiloso/Franco-arenoso Intoxicação /Massa seca Andrade et al, 2010;Andrade, 2008;Inoue et al, 2004;Inoue et al, 2011;Mendes et al, 2012;Silva et al, 2012;Silva, 2016 Silva et al, 2004 imazaquin Argiloso /Franco-argilo-arenoso Área foliar/Massa seca Inoue et al, 2000;Inoue et al, 2002 Carmo et al, 2008;Santos et al, 2013 Oryza sativa indaziflam Argilo-arenoso Dias et al, 2019 Panicum maximum isoxaflutole Argiloso/Franco-argilo-arenoso Intoxicação Marchiori Jr et al, 2005 Pennisetum glaucum Vianna et al, 1989 sulfentrazone Argiloso/Arenoso/Franco-argiloarenoso Intoxicação /Massa seca Belo et al, 2011;Dan et al, 2010;Faustino et al, 2015;Freitas et al, 2014;Melo et al, 2010;Silva, 2017;Teixeira et al, 2017 Sorghum vulgare atrazine Argiloso/Franco-arenoso Intoxicação /Massa seca/Área foliar Marchesan et al, 2011;Nunes e Vidal, 2009 indaziflam Arenoso/Argilo-arenoso Intoxicação /Massa seca Braga, 2017;Dias et al, 2019 Urochloa decumbens diuron Argiloso Massa seca Inoue et al, 2014 clomazone Arenoso/Argiloso Inoue et al, 2008;Mendes et al, 2012 diuron Arenoso/Argiloso/Argilo-arenoso indaziflam Argilo-arenoso Altura/Intoxicação /Massa seca Dias et al, 2019 isoxaflutole Argiloso/Franco-argilo-arenoso Intoxicação…”
Section: Seleção De Espécies Bioindicadorasunclassified